A study on the correlation between hyperuricemia and TG/HDL-c ratio in the Naxi ethnic group at high-altitude regions of Yunnan - Han, Dongmei; Yao, Yaqi; Wang, Fengshuang; He, Wenjing; Sun, Tianbao; Li, Han (Frontiers in Medicine, 2024)
Objective The study aimed to explore the risk factors for hyperuricemia (HUA) in the Naxi ethnic population residing in high-altitude areas of Yunnan, China, and assess the clinical value of the triglyceride/high-density lipoprotein cholesterol (TG/HDL-c) ratio as a diagnostic marker. Methods In this cross-sectional study, clinical data were collected from the health checkup population in the People's Hospital of Yulong Naxi Autonomous County, Yunnan Province, from January 2021 to January 2023. Participants were divided into quartiles based on the TG/HDL-c ratio (Q1, Q2, Q3, and Q4) for group analysis using chi-square tests, t-tests, and rank sum tests. Logistic regression analysis and linear regression models were employed to further investigate the correlation between the prevalence of hyperuricemia and TG/HDL-c ratio in this high-altitude Naxi population. Results A total of 714 participants from the health checkup population were included in the study, of whom 61.5% were male participants and 38.5% were female participants, and the average age was 41.21 ± 11.69 years. The mean uric acid level was 388.51 ± 99.24. After correcting for confounding factors, TG/HDL-c, serum creatinine (Scr), blood urea nitrogen (BUN), triglyceride (TG), high-density lipoprotein cholesterol (HDL-c), red blood cells (RBCs), and hemoglobin (Hb) showed a positive correlation with blood uric acid. Further analysis involved categorizing the TG/HDL-c ratio from a continuous variable to a categorical variable using quartiles. The fully adjusted model showed results that were consistent with the trend observed in the continuous variable analysis when considering the TG/HDL-c ratio as a categorical variable. In addition, in all unadjusted and adjusted models, the serum uric acid (SUA) levels in the high TG/HDL-c ratio group were significantly higher than those in the low TG/HDL-c ratio group (trend p < 0.001). Further linear relationship analysis indicated that after adjusting for covariates, there was an approximate linear relationship between the TG/HDL-c and SUA levels, with a coefficient (β) of 5.421. Conclusion The prevalence of hyperuricemia is greater in high-altitude areas of Yunnan, showing a nearly linear positive correlation with the TG/HDL-c ratio. Monitoring TG/HDL-c levels may benefit patients with hyperuricemia.